Effectiveness of 2 Weeks Administration of Potassium Competitive Acid Blocker vs Proton Pump Inhibitor Therapy in Patients with H. pylori Induced Gastritis in Pakistan: PCAB vs PPI Therapy in Patients with H. pylori Induced Gastritis - Iqbal, Muhammad Areeb; Khan, Khalid Mahmud; Shabbir, Ayesha; Tahir, Usman; Ahmad, Sadia; Rasheed, Nadia; Khalid, Samrah (Pakistan Journal of Health Sciences, 2026)
Helicobacter pylori cause major gastric and associated gastrointestinal complications, including gastritis and gastric malignancy. Latest evidence hints at the decline in the effectiveness of therapies having conventional proton pump inhibitors (PPI). Potassium competitive acid blockers (PCAB) have emerged as a potential option owing to longer and faster duration of action. However, limited data are available locally comparing PPI to PCAB-based therapies. Objectives: To compare and contrast the efficacy of two weeks of PCAB vs. PPI-based bismuth-containing quadruple therapy for H. pylori eradication. Methods: The quasi-experimental study conducted at the Department of Medicine, Jinnah Hospital, Lahore, recruited a total of 120 patients (60 in each group), aged 18-70 years, with confirmed H. pylori gastritis. Group A received Vonoprozan (PCAB) while Group B received Esomeprazole (PPI). Results: 86.67% of the patients achieved effectiveness in group A as compared to only 68.33% in group B, with a duration of symptoms of 8 weeks, almost similar in each group. The difference in effectiveness was statistically significant. (p=0.016). Conclusions: Vonoprazan (PCAB) based quadruple therapy is more effective at treating H. pylori-induced gastritis than Esomeprazole (PPI) containing therapies.